Strategi Dinas Pariwisata Dili Timor Leste untuk Meningkatkan Kunjungan Wisata di Objek wisata Pantai Area Branca - Ivana Francisca Joaquin Da Costa (Media Wisata, 2012)
The research was conducted at the Beach Area Branca attractions with the objective of identifying SWOT analysis conducted by the Office of Timor-Leste Dili tourism in developing the potential of Area Branca Beach attractions to increase tourist visits in Dili.This research uses a quantitative approach to analyze the strategies used and the SWOT analysis. From the survey results revealed that potential Beach Area attractions Branca towards ecotourism development by promoting nature tourism, maritime and land combined with up-tourism and cultural tourism. Constraints faced by the inadequate infrastructure, tourism organizations are not integrated, quality human resources are lacking and political conditions, the development of cooperation with the objects is done by outside parties and investors.